A critical take on procreative justice - Räsänen, Joona (John Wiley & Sons Ltd, 2025)
Herjeet Kaur Marway recently proposed the Principle of Procreative Justice, which says that reproducers have a strong moral obligation to avoid completing race and colour injustices through their selection choices. In this article, we analyze this principle and argue, appealing to a series of counterexamples, that some of the implications of Marway's Principle of Procreative Justice are difficult to accept. This casts doubt on whether the principle should be adopted. Also, we show that there are some more principled worries regarding Marway's idea of a strong pro tanto duty not to complete injustices through one's procreative choices. Nonetheless, we believe Marway's arguments point in the right general direction regarding duties and structural injustice. Thus, in the final part, we suggest a positive proposal on how it would be possible to respond to the cases we raise. More specifically, we explore the suggestion that agents have a pro tanto duty to participate in eliminating structural injustice. Importantly, this duty can be satisfied, not only in procreation choices but in multiple ways.